EFEKTIVITAS PENERAPAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DALAM MENINGKATKAN AKUNTABILITAS DAN TRANSPARANSI LAPORAN KEUANGAN DESA GRATI KECAMATAN SUMBERSUKO KABUPATEN LUMAJANG - Mutiara Mardaw; M. Cholid Mawardi; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The village government is required to compile a report on the realization of the APBDes and an Accountability Report on the Realization of the Implementation of the APBDes which is a form of accountability for the performance of the local government to the community which is used to assess the performance results of the village apparatus and as a medium to show transparency and accountability in village financial management. The purpose of this study was to determine the effectiveness of implementing the Village Financial System Application in increasing accountability and transparency of financial reports in Grati Village, Sumbersuko District, Lumajang Regency. This research method uses a qualitative approach with a qualitative descriptive type of research. The results of this study indicate that the application of the Village Financial System Application (SISKEUDES) is effective in increasing the accountability and transparency of financial reports in Grati Village, Sumbersuko District, Lumajang Regency.Keywords: Effectiveness, SISKEUDES, , Accountability, Transparency.